ON GENERIC TYPE SPECIES INDICATED BY MISAPPLIED NAMES - DONK, M. A. (REINWARDTIA, 1952)
When the type method was introduced in the "International Rules of Botanical Nomenclature," it was stated that "a nomenclatural type is that constituent element to which the name of a group is permanently attached" and, further, that "the type of ..a generic name is a species and that of a species ..is usually a specimen or preparation. In some species, however, the type is a description or figure given by a previous 1 author" (Art. 18).No doubt, the type of a generic name is a species and that of a specific name a specimen (or its substitute). A species may be variously interpreted as to its limits; it may be narrowly or broadly conceived. It may receive a name, but it remains a species even if it has no name. It frequently occurs that a specific name is misapplied to a quite different species. Hence it is also evident that a species and a specific name are two intrinsically different notions, not at all identical and interchangeable. As quoted above, Art. 18 positively says that the type of a generic name is a species and does not refer to specific names. I believe this article really states what it wanted to convey in this respect, and is not an instance of unfortunate wording. A species comprises a vast number of individuals plants and of these some are preserved often only in part, or are subject to taxonomic study without preservation,and represent the specimens of the Rules; when the species is given a name, one of these is or afterwards becomes the type specimen. Thus a (type) species and a (type) specimen are different notions. In the binomial system a specific name is a combination of two words. The first part, or generic appellation, stands for a generic description,2 the second part, or specific epithet, for a specific description : a specific name roots in two different descriptions.Far more often than not these two are published on different occasions by different authors.